Antigen- and receptor-driven regulatory mechanisms. I. Induction of suppressor T cells with anti-idiotypic antibodies (The Rockefeller University Press, 1979)
Delayed-type hypersensitivity (DTH) to the azobenzenearsonate (ABA) hapten can be readily induced in A/J mice injecting ABA-coupled syngeneic spleen cells subcutaneously. To further characterize this T- cell-dependent immunological phenomenon, the effect of passively administered anti-cross-reactive idiotype common to anti-ABA antibodies of A/J mice (CRI) antibodies on the development of ABA-specific DTH was investigated. Animals given daily injections (of minute amounts) of anti-CRI antibodies subsequent to immunization with ABA-coupled cells show significant reduction of ABA specific responses. This inhibition is antigen specific and requires the intact immunoglobulin molecule, as F(ab')2 treatments were ineffective in suppressing the reaction. Investigations of the mechanism of the anti-CRI-induced suppression of ABA DTH revealed that the observed suppression is a result of the activation of suppressor cells. Spleen cells taken from animals which received anti-CRI antibodies were able to adoptively transfer suppression to naive recipients. This suppression was shown to be mediated by T cells, as anti-Thy1.2 plus complement completely abrogated the transfer of suppression. In addition, animals pretreated with low doses of cyclophosphamide were not suppressed by the administration of anti-CRI antibodies. The genetic restriction of anti- CRI-induced suppression was demonstrated. Antibodies to the major cross- reactive idiotype, (CRI) associated with anti-ABA antibodies in A/J mice were unable to suppress the development of DTH to ABA in BALB/c mice (H-2d, Igh-1a). Such antibodies were, however, fully active in suppressing ABA DTH in the allotype-congenic C.AL-20 strain which has an allotype (Igh-1d) similar to that of A/J (Igh-1e) on a BALB/c background, and which produces humoral antibodies with the CRI.